Characterization of TiN films sputter-deposited at low temperatures for Cu-through-silicon via. (25th February 2019) - Sato, Masaru; Kitada, Hideki; Takeyama, Mayumi B.
Abstract: We examined a low-temperature-deposited TiN film on an SiO2 /Si substrate as a diffusion barrier applicable to a Cu-through-silicon via structure. We successfully prepared the TiN films with (100) orientation even on an SiO2 layer in an amorphous state. The (100)-oriented TiN film showed good barrier properties, too. The reason for these results may be the possible suppression of both recrystallization of the barrier and Cu diffusion by having several fiber structures.